The conversion of bioethanol from pineapple waste to biobutanol derivatives over NiMoO4/rGo catalyst - Allwar Allwar; R. B. S. Ningrum; Alya Imanya; Adinda Zulfaati Rahma (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Increasing demand for sustainable energy solutions has spurred the development of catalytic materials to convert renewable resources into value-added hydrocarbons. In this work, we investigate the feasibility of NiMoO4/rGo as an effective catalyst for converting bioethanol into renewable hydrocarbons. The surface and microstructural characteristics of rGo showed major findings like BET surface area of 26.9 m2/g with mesoporous, sufficient surface functional groups, crystalline size of 49.12 nm, and a progressive metal oxide uniform distribution on the rGo surface. The crystal morphology showed an irregular texture, suggesting strong catalytic activity. The optimal conversion was thus observed at 80°C, 90°C, and 100°C. Superior catalytic activity at 80°C afforded the resultant three major hydrocarbon-based products: 2-butanol (1.32%), isobutyl alcohol (0.89%), and 3-methyl-1-butanol (0.89%). Such products have important potential as renewable substitutes in diverse industries. Our study highlights the potential of using NiMoO4/rGo as an effective catalyst for bioethanol conversion due to its mesoporous structure, oxygen groups, and high dispersion of active metal oxide. Overall, this study renders NiMoO4/rGo a viable catalyst candidate in sustainable chemical processes and thus accelerates the application of bioethanol to manufacture precious hydrocarbon derivatives. These findings underscore the key to optimizing temperature conditions to maximize product yield and enhance the economic viability of renewable energy resources.